Robust vision for vision-based control of motion - Hager, Gregory D., 1961-; Vincze, Markus, 1965-; John Wiley & Sons; IEEE Robotics and Automation Society; IEEE Xplore (Online service) (Bellingham, Wash. : SPIE Optical Engineering Press, 2000)
Find the design principles you need to move vision-based control out of the lab and into the real world. In this edited collection of state-of-the-art papers, contributors highly regarded in robust vision bring you the latest applications in the field. Whatever your industry - from space ventures to mobile surveillance - you will discover throughout this comprehensive collection a strong emphasis on robust vision simply unmatched today. You will also gain an in-depth analysis of vision techniques used to control the motion of robots and machines. Expert contributors offer you key insights into: . Current control issues including hardware design, system architecture, sensor data fusion, and visual tracking. Modeling methods for vision-based sensing. Useful summaries of recent conclusions drawn from robust-vision workshops. Future research needs If you want to learn today's approaches to robust vision-based control of motion, this extensive collection is a must. Learn from the experts and, in the process, speed your project development and broaden your technical expertise for future collaborative efforts in your industry.
13.3 Directed Image Processing and Adaptive Windowing -- 13.4 Feature Planning and Selection -- 13.5 Information Redundancy and Sensor Integration -- 13.6 Conclusions -- CHAPTER 14 VISION-BASED OBJECTIVE SELECTION FOR ROBUST BALLISTIC MANIPULATION (Bradley E. Bishop, and Mark W. Spong) -- 14.1 Introduction -- 14.2 Visual Measurement Scheme -- 14.3 State Estimation and Prediction -- 14.4 Air Hockey -- 14.5 Conclusions and Future Work -- 14.6 Acknowledgments -- CHAPTER 15 VISION-BASED AUTONOMOUS HELICOPTER RESEARCH AT CARNEGIE MELLON ROBOTICS INSTITUTE (1991-1998) (Omead Amidi, Takeo Kanade, and Ryan Miller) -- 15.1 Introduction -- 15.2 Goals -- 15.3 Capabilities -- 15.4 Future Work -- INDEX -- ABOUT THE EDITORS.
"IEEE Robotics and Automation Society, sponsor."
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/21/2015.
Keywords: Robot vision; Robots -- Control systems; Robots -- Motion; Electronic books